An acute bout of high intensity interval training reduces the autophagosome content in type I and Type II muscle fibres - Shaw, C. S.; Zacharewicz, E.; Trewin, A. J.; Parker, L.; Garnham, A.; Stepto, N. K.; Murphy, R. M. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Autophagy is a dynamic intracellular degradation process which can target old or damaged organelles and provide substrate for cellular regeneration. Activation of autophagy during exercise has been implicated in the improvements in glucose homeostasis with training. The aim of this study was to investigate the muscle fibre type specific autophagy response to an acute bout of moderate intensity continuous (MICT) and high intensity interval training (HIT). Methods: Eight recreationally active individuals (aged 25±6 years, BMI 24.8±1.0, VO2max 48.4±4.0 ml/min/kg) completed two exercise bouts on a cycle ergometer in a randomised order separated by 7 days. HIT sessions involved 5 x 4 min bouts performed at 75% peak power output whereas MICT was performed at 50% of peak power output, work matched to the HIT session. Muscle biopsies were collected after an overnight fast prior to exercise, immediately postexercise and 3 h post-exercise. Single muscle fibres were immediately isolated and muscle fibre type was assessed using immunoblotting. Single muscle fibres of the same fibre type were pooled before analysis of the autophagy markers LC3-I/II, GABARAP and p62. Results: Basal LC3-II abundance (P=0.08) and the LC3-II/I ratio (P<0.05) was higher in type I muscle fibres, which is indicative of greater autophagosome content. There was no significant change in LC3-II abundance or LC3-II/I ratio in response to MICT immediately or 3 hours post-exercise. In contrast, there was a reduction in the LC3-II abundance in type I (P=0.02) and type II muscle fibres (P=0.02) immediately post-HIT which returned to baseline values at 3 hours post-exercise. These changes were reflected in the LC3-II/I ratio which were also reduced in both muscle fibre types immediately following HIT (P<0.05). There were no significant differences in GABARAP or p62 abundance (P>0.05) following either exercise mode (P>0.05). Discussion: These results demonstrate that HIT induces a transient reduction in autophagosome content in both type I and type II muscle fibres which does not occur following a work matched bout of MICT. This enhanced clearance of autophagosomes may contribute to the superior metabolic benefits observed following HIT. Furthermore, these results indicate that type I muscle fibres have a higher autophagosome content in the basal state, therefore fibre type differences should be considered when assessing autophagy in human skeletal muscle.